Disparitas Putusan Pengadilan Agama Terhadap Legal Standing LPKSM Sebagai Penggugat Dalam Sengketa Ekonomi Syariah - Alifia, Putri; Rohman, Muhammad Mujibur (JOURNAL of LEGAL RESEARCH, 2024)
The inconsistency of decisions regarding the legal standing of the Community-Based Consumer Protection Institution (LPKSM) in the Sharia economic court case at the Religious Court has created legal defenders. There are differences of opinion between judges regarding the legal standing of LPKSM as the Plaintiff in this settlement. This study aims to examine the position of LPKSM in the trial at the Religious Court and analyze various decisions that show this disparity. Through a qualitative literature approach, the study concludes that the law grants LPKSM the right to sue with specific requirements. LPKSM cannot act as an advocate representing consumers directly because it contradicts Law Number 18 of 2013. The differences in court decisions regarding the legal standing of LPKSM mainly depend on considerations regarding the interests fought for by the institution. To overcome the disparity in decisions and create legal certainty, a special formulation is needed to be used as a guideline in reconstructing the sharia economy. LPKSM who wish to become a party in a Sharia economic case must meet formal and material requirements, namely being a legal entity or foundation, having Articles of Association, being registered with the Consumer Protection Agency Registration Certificate (TDLP), and fighting for public interests, not individual interests. With clear standards, it is hoped that legal certainty can be created in handling Sharia economic settlements involving LPKSM in the Religious Court.